Legal Liability of AI Developers for Individual Interactions with Chatbots Resulting in Death: A Comparative Study - Khairunnisa Maharani; Sinta Dewi Rosadi; Nella Sumika Putri (PDIH Untag Semarang, 2025)
The development and use of Artificial Intelligence (AI) in platforms such as chatbots has raised ethical and legal concerns. This study aims to examine the legal responsibilities of AI developers, focusing on the case of Garcia Vs. Character Technologies, in which a teenager’s death was allegedly influenced by interaction with an AI chatbot. This study compares Indonesian and European Union legal frameworks on AI developer liability for harms arising from chatbot interactions. This study is a legal study that uses a normative juridical approach by conducting a review of legislation and comparing laws with other countries to answer the research questions. The results show that the regulation of AI ethics in Indonesia is still developing and relies on the Electronic Information and Transactions Law and the Personal Data Protection Law, which do not specifically regulate AI, while the European Union already has more comprehensive regulations. The responsibilities of AI developers, such as those in chatbot platforms, include ensuring system security from physical or psychological impacts, protecting personal data, and ensuring fair and transparent algorithms. Universally, both in Indonesia and the European Union, developers are required to comply with the principles of safety, fairness, and human rights by conducting testing to avoid bias and negative impacts on users.